Y3−x(Al0·9In0·1)5O12:Eu: preparation, structure effect on luminescent properties. (May 2014) - Zhang, W.; Liang, Y. L.; Hu, Z. F.; Feng, Z. Y.; Liu, S. X.; Sheng, X.
<x content-type="archive" xml:space="preserve">Abstract</x> The single phase of Eu doped YAIG [Y3−x(Al0·9In0·1)5O12:<inline-graphic xlink:href="ark:/27927/pghjnrz189" xmlns:xlink="http://www.w3.org/1999/xlink" />] powder was synthesised at 1000°C by using the coprecipitation method. The influence of phase structure and Eu doping concentration on luminescence properties was investigated using TGA, XRD, SEM and XPS. The results indicate that the coprecipitation method promotes the formation of ultrafine powders and partial substitution of In3+ for Al3+, leading to a slight left shift of the related peak in the XRD spectra. In addition, with the ascent of Eu3+ concentration, the emission intensity of the sample also increases significantly.